THE SIGNIFICANCE OF THE MINOR CHARACTER IN ROWLING S HARRY POTTER AND THE ORDER OF THE PHOENIX - Kindangen, Mela Rauna; Mogea, Tini; Maukar, Merlin (Journal of English Culture, Language, Literature and Education, 2022)
Literary works is a form of someone s creation that has meaning or has a purpose by the author Literary as a result of human creation will never be separated from language which is the main medium in literary works This research aims to analyze the minor character Luna Lovegood using qualitative research method based on the theory of Robert Stanton Stanton said that there are four ways to analyze a character: character s words character s behavior conversations between character and character s action The writer uses an intrinsic approach to analyze the character of Luna Lovegood The data taken from the novel by J K Rowling Harry Potter and the Order of the Phoenix After conducting research on the novel Harry Potter and the Order of the Phoenix the findings obtained by the writer regarding the character of Luna Lovegood are Luna has characters such as appreciation of beauty and excellence which is obtained based on character s words Kindness obtained based on character s behavior Bravery curiosity and humility obtained based on the conversations between character And kindness bravery too also found based on character s action< p>